Benthic primary production in an upwelling-influenced coral reef, Colombian Caribbean - Eidens, Corvin; Bayraktarov, Elisa; Hauffe, Torsten; Pizarro, Valeria; Wilke, Thomas; Wild, Christian (PeerJ, 2014)
In Tayrona National Natural Park (Colombian Caribbean), abiotic factors such as light intensity, water temperature, and nutrient availability are subjected to high temporal variability due to seasonal coastal upwelling. These factors are the major drivers controlling coral reef primary production as one of the key ecosystem services. This offers the opportunity to assess the effects of abiotic factors on reef productivity. We therefore quantified primary net (Pn) and gross production (Pg) of the dominant local primary producers (scleractinian corals, macroalgae, algal turfs, crustose coralline algae, and microphytobenthos) at a water current/wave-exposed and-sheltered site in an exemplary bay of Tayrona National Natural Park. A series of short-term incubations was conducted to quantify O2 fluxes of the different primary producers during non-upwelling and the upwelling event 2011/2012, and generalized linear models were used to analyze group-specific O2 production, their contribution to benthic O2 fluxes, and total daily benthic O2 production. At the organism level, scleractinian corals showed highest Pn and Pg rates during non-upwelling (16 and 19 mmol O2 m−2 specimen area h−1), and corals and algal turfs dominated the primary production during upwelling (12 and 19 mmol O2 m−2 specimen area h−1, respectively). At the ecosystem level, corals contributed most to total Pn and Pg during non-upwelling, while during upwelling, corals contributed most to Pn and Pg only at the exposed site and macroalgae at the sheltered site, respectively. Despite the significant spatial and temporal differences in individual productivity of the investigated groups and their different contribution to reef productivity, differences for daily ecosystem productivity were only present for Pg at exposed with higher O2 fluxes during non-upwelling compared to upwelling. Our findings therefore indicate that total benthic primary productivity of local autotrophic reef communities is relatively stable despite the pronounced fluctuations of environmental key parameters. This may result in higher resilience against anthropogenic disturbances and climate change and Tayrona National Natural Park should therefore be considered as a conservation priority area.
Keywords: O2 flux; Ecosystem productivity; Resilience; Coastal upwelling; Seasonal variation; Tayrona National Natural Park